Thionated aminofluorophthalimides reduce classical markers of cellular inflammation in LPS-challenged RAW 264.7 cells. (15th November 2022) - Scerba, Michael T.; Tweedie, David; Lecca, Daniela; Siegler, Maxime A.; Rais, Rana; Greig, Nigel H.
Graphical abstract: Abstract: Herein, we present the synthesis of several fluorinated pomalidomide derivatives and their thionated counterparts with subsequent biological evaluation against classical markers of cellular inflammation. Treatment in LPS-challenged cells effected varying reductions in levels of secreted TNF-α and nitrite relative to basal amounts. While arene fluorination and thioamidation had marginal and sporadic effects on TNF-α production, specific 7-position fluorination combined with subsequent increases in carbonyl thionation produced compounds 11, 14, and 15 which demonstrated corresponding and escalating anti-nitrite activities concurrent with minimal cellular toxicity. In this regard, compound 15 displayed roughly 96 % cell viability combined with a 65 % drop in nitrite production when supplied to RAW cells challenged with 60 ng/mL LPS. When a focused family of fluorinated isomers were directly compared, the analogous 5-fluorinated isomer 17 displayed comparable minimal toxicity but markedly less anti-nitrite activity versus 15 in RAW cells challenged with 70 ng/mL LPS. Compound 15 was subsequently screened in human liver microsomes for preliminary Phase 1 analysis where it demonstrated heightened stability relative to its non-fluorinated counterpart 3, 6′-dithiopomalidomide 4, a result in line with the expected metabolic fortitude provided by fluorination at the sensitive pomalidomide 7-position.